Influência do tamanho e umidade do grão na expansão da pipoca South American Mushroom - Sawazaki, Eduardo; Morais, Jener Fernando Leite De [UNESP]; Lago, Antonio Augusto Do (Instituto Agronômico de Campinas, 1986)
The effect of grain size and moisture on the popping expansion of popcorn was evaluated for the cultivar South American Mushroom, produced in 1984/85, in Campinas, São Paulo, Brazil. Grain size classes ranging from 14/64 to 18/64 inch, and moisture contents from 9.4 to 19.8% were studied. The results indicated a higher expansion rate for the smaller grains and for moisture contents between 10.5 and 11.5%.

Utilizando sementes do cultivar de milho-pipoca South American Mushroom, obtido em 1984/85 em Campinas, SP, procurou-se avaliar os efeitos do teor de umidade e tamanho de grão na expansão da pipoca. Foram empregados tamanhos de grãos compreendidos entre as peneiras 14 e 18 e teores de umidade entre 9,4 e 19,8%. Os resultados mostraram que a capacidade de expansão foi maior nos grãos menores e nos teores de umidade de 10,5 a 11,5%.
Influence of size and moisture of grain on the popping expansion of the cultivar South American Mushroom popcorn
Keywords: popcorn; grain size and moisture; popping expansion; milho-pipoca; grão; tamanho; umidade e capacidade de expansão